Anal Pruritus: Diagnosis and Management - Daniel T. Slagle; William J. Harb (World Journal of Colorectal Surgery)
Pruritus ani is a condition that results in itching or burning in the perianal area. It can be due to primary or secondary causes and can be self-limiting or persistent. To date, there is limited quality evidence in the literature, and there are no published guidelines to aid the physician in its diagnosis and management. In this article, an overview of the current literature is discussed and a suggested treatment algorithm is provided. A thorough history and physical examination is essential to rule out secondary causes of pruritus. The underlying etiology of pruritus guides management. Education regarding anal hygiene is important for all cases. For any patient with refractory pruritus or an abnormal exam, biopsy should be strongly considered.